The Use of Invisalign® System in the Management of the Orthodontic Treatment before and after Class III Surgical Approach - Renato Pagani; Fabrizio Signorino; Pier Paolo Poli; Pietro Manzini; Irene Panisi (Hindawi Limited, 2016)
The approach to skeletal dysmorphisms in the maxillofacial area usually requires an orthodontic treatment by means of fixed appliances, both before and after the surgical phase. Since its introduction, Invisalign system has become a popular treatment choice for the clinicians because of the aesthetics and comfort of the removable clear aligners compared with the traditional appliances. Therefore, the aim of the present report was to illustrate the management of a malocclusion by means of Invisalign system associated with the traditional surgical technique. The present paper shows a case of a 23-year-old male patient characterized by a Class III malocclusion with lateral deviation of the mandible to the left side and cross-bite on teeth 2.2, 2.3, and 2.4. Invisalign system was used during the pre- and postsurgical phases rather than fixed appliances. The posttreatment cephalometric analysis emphasized the stability of the dental and skeletal symmetry corrections, occlusion and functional balance, over a 6-year follow-up. The results achieved at the end of the treatment showed how Invisalign can be effective in the management of the orthodontic phases in orthognathic surgery. The follow-up after 6 years emphasizes the stability of the treatment over time.